Revisiting the asymmetry between the exchange rate and domestic production in South Asian economies: Evidence from nonlinear ARDL approach - Javed Iqbal; Misbah Nosheen; Mark Wohar (Universitas Islam Indonesia, 2022)
Purpose ― The present study investigates the asymmetric effect of exchange rate changes on the domestic production of selected South Asian economies from 1980-2019. Design/Method/Approach―The study introduces nonlinearity into the adjustment process by decomposing the exchange rate into depreciation and appreciation and relying on the Nonlinear ARDL approach to cointegration. Findings ― The findings show significant evidence of asymmetric effects of exchange rate changes on domestic production in the case of South Asian economies. Surprisingly, depreciation promotes economic growth while appreciation impedes it in almost all economies. Practical Implications ― The findings refute the notion of symmetry, indicating that depreciation and appreciation have different effects on South Asian economies. An undervalued exchange rate may provide short-term economic relief. The study recommends that a market-based equilibrium exchange rate is crucial for these economies. Originality/Value ― By using a Nonlinear ARDL approach to separate exchange rate appreciation and depreciation, this study adds to the body of knowledge about the relationship between exchange rate and growth, particularly in South Asia.